The separation of beef meat according to the quality and slicing in Athens - ΚΟΥΤΡΑΣ, ΝΙΚΟΛΑΟΣ (Journal of the Hellenic Veterinary Medical Society, 2019)
The Author gives the definition of the quality separation of beef meat in three classes. Also he reffers to the stages of slicing of the beef meat and he describes the cuts of carcasse as is done in practice in the Athenian market